Reificação e totalidade à luz de história e consciência de classe (1923) de György Lukács - Almeida, Roberto Ribeiro de (2012)
This dissertation intends to further study the phenomenon of reification and its relation to the category Totality, outlining the approach in the light of the concepts outlined in History and Class Consciousness (1923) by György Lukács, prepared by collection of literature, architected to point the effects of commodity fetishism as a mediator of social relations (reification), constitutes a specific reality and seemingly insurmountable to those who live under modern capitalism. With the homogenization of the capitalist mode of production, under the aegis of increasing specialization and rationalization of the mechanized work process, mankind has been organized to produce and meet their needs through the exchange of goods, placing individuals, who have to relate to things, a state of confrontation and contemplation of its activities. This research presents the views and vicissitudes of a work in context, the heart of which was to show that the unveiling of the ways the structure of the commodity fetish, the proletarian cause, the consciousness of their class condition, from which it could grasp the whole historical of social reality, the question of the party as mediator of active consciousness, and thereby establish benchmarks legitimate revolutionary action, beyond the reified conceptions of social transformation, and thus, says Lukacs, lead humanity to a higher step of its development, with ownership and conscious control of production, which is possible only with the abolition of the capitalist mode of production